MODELAGEM DO USUÁRIO PARA O SISTEMA ICS DE COMÉRCIO ELETRÔNICO - Bastos Filho, Othon de Carvalho (2003)
The Electronic Commerce (E-commerce) grew very in recent years. This type of Commerce, call also digital or virtual commerce, is characterized for the increasing capacity of supply, global competition, increasing, with this, the expectations of the consumers, thus causing, one high competition between the companies, who very change of fast form the businesses and the way to operate. Being that, it can be perceived that the companies who will not be ready for the changes, in a short period had been it stops backwards in the world of the businesses. The Electronic Commerce allows that such changes can be supported in one it scales global, making possible a bigger efficiency and flexibility, this occurs by means of the agility in taking care of to the necessities and expectations of the customers. For this new paradigm, it currently starts if to legalize the business-oriented call Intelligence (Business Intelligence), whose purpose is to manage the knowledge in the age of the global competition and the communications on-line.